1993
DOI: 10.1128/jvi.67.2.791-800.1993
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the interferon-induced 68,000-M(r) protein kinase by poliovirus requires RNA

Abstract: Control of the interferon-induced double-stranded RNA (dsRNA) activated protein kinase (referred to as P68 because of its Mr of 68,000 in human cells) by animal viruses is essential to avoid decreases in protein synthetic rates during infection. We have previously demonstrated that poliovirus establishes a unique way of regulating the protein kinase, namely by inducing the specific degradation of P68 during infection (T. L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…by squelching activator dsRNAs Davies et al, 1993). Poliovirus has been shown to recruit a cellular protease that apparently works in conjunction with poliovirus-specific dsRNA to degrade PKR (Black et al, 1993). Influenza virus also triggers a host cell protein (p58) that is a member of the tetratricopeptide repeat (TPR) family of proteins to down-regulate PKR (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…by squelching activator dsRNAs Davies et al, 1993). Poliovirus has been shown to recruit a cellular protease that apparently works in conjunction with poliovirus-specific dsRNA to degrade PKR (Black et al, 1993). Influenza virus also triggers a host cell protein (p58) that is a member of the tetratricopeptide repeat (TPR) family of proteins to down-regulate PKR (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although many viruses suppress PKR function using various strategies [32], poliovirus is known to promote PKR degradation in infected cells [60,61]; poliovirus RNA and viral protein components are required for this activity [61], and both eIF2a and PKR are highly activated in poliovirus-infected cells before PKR downregulation occurs [60]. In contrast to poliovirus, only RVFV NSs protein was probably required for PKR downregu-lation since the downregulation of PKR occurred as early as 4 h.p.i.…”
Section: Possible Mechanisms Of the Nss-mediated Pkr Downregulationmentioning
confidence: 99%
“…236 The detailed mechanism of this degradation is not fully understood, although it has been suggested that cellular rather than viral proteases are required. 237 Finally, it has been shown recently that the NSs protein of rift valley fever virus (RVFV) induces specific degradation of PKR. 238 Following infection with RVFV there is a dramatic decrease in PKR protein levels with little change in the levels of the mRNA.…”
Section: Degradation Of Pkrmentioning
confidence: 99%